Impact of Healthcare Accessibility on the Quality of Life of Older Adults in China and Its Age Differences - Lie Zhao; Huiqin Yang (SAGE Open)
With the accelerating aging of the population, the accessibility of healthcare services has become a critical factor affecting the quality of life of older adults. Based on data from the 2018 Chinese Longitudinal Healthy Longevity Survey, this study analyzes 12,115 older adults (Mean = 84.27 years old, Standard Deviation = 11.38), using coefficient clustering method to quantify the impact effects and their magnitudes. This study explores the effect strength of opportunities for older adults to access, obtain, and utilize healthcare services on their quality of life, as well as the age differences in these effects. The empirical results show that: (1) Both subjective and objective healthcare accessibility significantly improve older adults’ quality of life, with subjective accessibility consistently showing stronger effects across age groups (60–69, 70–79, 80–89, and ≥90 years old). (2) Among different age groups, The effect strength of subjective healthcare accessibility shows a first Increase and then decrease trend, while the effect strength of objective healthcare accessibility gradually decrease. (3) The disparity in effect size between the two types of healthcare accessibility further widens among the oldest age groups, increasing from 1.1 to 4.1 times, this suggests that for the oldest-old, there is a greater emphasis on shifting healthcare service resources from “passive accessibility” to “proactive service.” The findings provide empirical evidence for the development of age-stratified healthcare service policies, they contribute to more precisely addressing the diverse healthcare needs of older adults in China and other developing countries, thereby effectively enhancing their quality of life.